A typology of insurgent, terrorist and extremist threats in India. Issue 2 (4th May 2018) - Siyech, Mohammed Sinan
ABSTRACT: India's threat landscape is dotted with various groups fighting for multiple causes. This article attempts to provide an overview of the most prominent groups that operate all over the nation. In this respect, it casts light on the Kashmiri Conflict, the Naxalite Insurgency, the North-East Separatist groups, Islamist threats and the Hindutva extremism. Key aspects of the groups covered here include their origin, membership, facilitating factors and government response among others. This article analyses the Kashmiri, Naxalite and North-East militancy as insurgent groups whereas it analyses the rise and fall of Islamist and Hindu extremism through the lens of identity theories.